Experimental assessment of fluid-to-fluid scaling for critical heat flux investigations in rod bundles at low mass flow - García, A.E.; Marcel, Christian Pablo; Delmastro, Dario Fabian (Elsevier Science SA, 2022)
Fil: García, A.E.. Comisión Nacional de Energía Atómica. Gerencia del Área de Energía Nuclear. Instituto Balseiro; Argentina. Comisión Nacional de Energía Atómica; Argentina